Genomic Resources for Salminus brasiliensis - Graciano, Raissa Cristina Dias; Oliveira, Rafael Sachetto; Santos, Isllas Miguel; Yazbeck, Gabriel M. (Frontiers in Genetics, 2022)
The Neotropical region bears the most diverse freshwater fish fauna on the planet and is the stage for dramatic conservation struggles. Initiatives aiming for conservation of a single emblematic fish, a flagship species, to which different onlookers relate on a cultural/personal level, holds promise towards engagement and conservation actions benefiting whole biological communities and ecosystems. Here, we present the first comprehensive genomic resources for Salminus brasiliensis, a potential flagship Neotropical species. This fish faces pressing conservation issues, as well as taxonomic uncertainty, being a main species relevant to angling and commercial fisheries. We make available 178 million Illumina paired-end reads, 90 bases long, comprising 16 Gb (≈15X coverage) of filtered data, obtained from a primary genomic library of 500-bp fragments. We present the first de novo genomic assembly for S. brasiliensis, with ∼1 Gb (N50 = 10,889), as well as the coding genome annotation of 12,962 putative genes from assembled genomic fragments over 10 kb, most of which could be identified from the Ostariophysi GenBank database. We also provide a genome-wide panel for more than 80,000 predicted microsatellite loci for low-cost, fast and abundant DNA marker development for this species. A total of 47, among 52 candidates, empirically assayed microsatellites were confirmed as polymorphic in this fish. All genomic data produced for S. brasiliensis is hereby made publicly accessible. With the disclosure of these results, we intend to foster general biology studies and to provide tools to be applied immediately in conservation and aquaculture in this candidate flagship Neotropical species.